Structural Disorder and Electron Transport in Graphene at Low Temperatures; AIP Conference Proceedings; Vol. 1909 : Advanced Materials with Hierarchical Structure for New Technologies and Reliable Structures 2017 (AMHS’17) - Bobenko N. G. Nadezhda Georgievna; Egorushkin V. E.; Melnikova N. V.; Ponomarev A. N. Aleksandr Nikolaevich; Belosludtseva A. A.; Barkalov L. D. (2017, 2017)
Title screen